Analisis Pelanggaran Etika Profesi Akuntan (Studi Kasus PT Antam Tbk) - Dwi Putri, Syahwa Amanda; Santika, Tarisa Mita; Putri, Auli Nanda; Nusema, Yulialda; Saridawati (Journal of Business and Halal Industry, 2024)
Corruptio” is another word for corruption which means danger, crime, depravity, fraud and immorality. This research intends to understand corruption cases from the ethical perspective of the accounting profession. This research uses qualitative methods. Data sources are obtained from data collected as secondary data. From this discussion, the researcher concluded that there were 4 frauds committed based on the agreement to carry out illegal mining at WIUP PT Antam Tbk.